Self-Help, Inc. makeover culture in American life - McGee, Micki (New York ; Oxford : Oxford University Press, 2005)
Why doesn't self-help help? Micki McGee explores the demand for self-help & what it tells us about ourselves.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Self-help techniques -- United States; Psychological literature -- United States; Success -- United States -- Psychological aspects